Dynamics of Intestinal Inflammatory Cytokines and Tight Junction Proteins of Turbot (Scophthalmus maximus L.) During the Development and Recovery of Enteritis Induced by Dietary β-Conglycinin - Jing Zheng (Frontiers in Marine Science, 2020)
This study was conducted to investigate the dynamic characterization of enteritis of juvenile turbot (Scophthalmus maximus L.) during the development of enteritis induced by dietary β-conglycinin (7S) and the recovery by fish meal (FM). Two isonitrogenous and isolipidic experimental diets were formulated, FM diet and FM supplemented with 8% 7S diet. The feeding trial consists of three groups, turbot fed FM and 7S diet for 10 weeks, respectively, and turbot fed 7S diet for 3 weeks and then fed FM diet for another 7 weeks (7S&FM). The distal intestines and serum of turbot in the 7S&FM group were sampled at the zeroth day, third day, first week, second week, third week, sixth week, and tenth week. At the end of the feeding trial, the growth performance and feed utilization of turbot in the FM and 7S&FM group were significantly higher than that of turbot in the 7S group. According to the observation of intestinal histology, the typical symptoms of enteritis were observed at the third week and then mitigated by FM gradually until the tenth week. The activities of diamine oxidase (DAO) and content of D-lactate in serum showed a similar trend in 10 weeks. The gene expression of pro-inflammatory cytokines IL-1β, IL-8, IL-22, and IFN-γ was significantly increased by 7S in the first 3 weeks and then significantly decreased by FM since the sixth week, as well as the expression of NF-κB p65. The opposite trend of gene expression was observed in anti-inflammatory cytokine TGF-β. The gene expression of tight junction proteins claudin-3, claudin-4, claudin-like, occludin, and ZO-1 was significantly decreased during the first 3 weeks and then the gene expression of claudin-4 and occludin was significantly increased by dietary FM since the sixth week. Meanwhile, the gene expression of myosin light chain kinase (MLCK) increased significantly during the first 3 weeks and then significantly declined at the tenth week. Collectively, dietary 8% 7S could induce the serious enteritis of turbot in 3 weeks and the mitigation progress could be observed when turbot are fed with FM diet. The intestinal inflammatory cytokines and tight junction proteins showed different responses during the development and recovery of enteritis.